Induction in Adult Acute Lymphoblastic Leukaemia: A Study of 22 Cases - Khatun, Hazera; Morshed, Manzur; Anam, Sadia (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Treatment of acute lymphoblastic leukaemia yields high complete remission (CR) rate with disappointingly low overall survival. We describe the results of induction in 22 cases of adult acute lymphoblastic leukaemia treated between January 2011 and January 2013. Median age at presentation was 28 years (range 13-70). Fatigue (n=15, 68%) was the most frequent presenting complaint followed by fever (n=14, 63.7%). 36.3% patients presented with splenomegaly while 31.8% had lymphadenopathy. The average presenting white cell count was 61 k/ul. B-ALL was more common than TALL (59% and 27% respectively). 8 cases were deemed high risk and 14 cases were standard risk. One patient died early in induction before specific treatment. 20 patients were treated with intensive chemotherapy (CALGB8811=12, MCP 841=4, CCG-BFM=2 and BFM-90=1, others 1). Overall CR was 85% while CR in CALGB8811 was 83.3%.The average time to NADIR was 10 days (range 6 -17 days). The most common complication in induction was neutropenic sepsis (n=19, 86.4%) contributing alone to induction mortality of 15% (n=3). Causative organism was identified in only 31.8% cases (n=7), the commonest being pseudomonas and coagulase negative staphylococcus. Facilities for extended immunophenotyping and cytogenetic tests (in addition to BCR-ABL by PCR) are required for administration of standard of treatment. J Bangladesh Coll Phys Surg 2015; 33(1): 18-22